Assessing Sedation Depth with PSI in Elderly ERCP Patients: A Prospective Cohort Study - Huang L; Liu LL; Lu YD; Zhuang MY; Dou W; Liu H; Ji FH; Peng K (Clinical Interventions in Aging)
Lei Huang,1,2,* Lin-lin Liu,1,2,* Yong-da Lu,3,* Min-yuan Zhuang,1,2 Wei Dou,1,2 Hong Liu,4 Fu-hai Ji,1,2 Ke Peng1 1Department of Anesthesiology, First Affiliated Hospital of Soochow University, Suzhou, Jiangsu, People’s Republic of China; 2Institute of Anesthesiology, Soochow University, Suzhou, Jiangsu, People’s Republic of China; 3Department of Gastroenterology, First Affiliated Hospital of Soochow University, Suzhou, Jiangsu, People’s Republic of China; 4Department of Anesthesiology and Pain Medicine, University of California Davis Health, Sacramento, CA, USA*These authors contributed equally to this workCorrespondence: Ke Peng, Department of Anesthesiology, First Affiliated Hospital of Soochow University, 188 Shizi Street, Suzhou, Jiangsu, 215006, People’s Republic of China, Tel +86-512-67780056 ; +86-15962155989, Email pengke0422@163.comBackground: Adequate sedation is important for elderly patients undergoing endoscopic retrograde cholangiopancreatography (ERCP). Patient state index (PSI) via the SedLine® system has been utilized for real-time monitoring of anesthesia depth in surgical patients. We aimed to assess the correlation between PSI and Modified Observer’s Assessment of Alertness/Sedation (MOAA/S) scores in elderly patients undergoing ERCP.Methods: This prospective cohort study included 57 elderly patients scheduled for ERCP procedures. Patients received target-controlled infusion of propofol, titrated to the sedation level of MOAA/S scores of 1 and 2. The MOAA/S scores and PSI values were recorded during sedation and recovery. We also documented procedure and recovery time, oversedation (PSI < 25 for at least 10 min and EEG burst suppression), adverse events, and fatigue scores (0– 10, higher scores indicating more fatigue).Results: All patients completed this study (mean age of 73 years and 63% male), with a mean procedure time of 53 min and recovery time of 37 min. Five patients (8.8%) experienced PSI < 25 for at least 10 min, and three of them (5.3%) showed EEG burst suppression. No patients developed desaturation or intra-procedural awareness. Hypotension and abdominal pain were uncommon. Nine patients (15.8%) experienced mild dizziness or nausea. The median (IQR) fatigue score was 3 (2– 4) at recovery room discharge. A significant correlation was observed between the MOAA/S scores and PSI values (Spearman correlation coefficient ρ = 0.742, P < 0.001). When patients were at the MOAA/S scores of 1 and 2, the median PSI was 50 (95% CI: 48 to 52).Conclusion: PSI provides a useful and real-time monitoring of sedation for elderly patients undergoing ERCP. Our results showed a significant correlation between the PSI values and MOAA/S scores and suggested a PSI value of 50 with a range of 48 to 52 for maintaining adequate sedation.Trial Registration: Chinese Clinical Trial Registry (ChiCTR2400079859).Keywords: endoscopic retrograde cholangiopancreatography, depth of sedation, elderly patients, Modified Observer’s Assessment of Alertness/Sedation, patient state index